THE PRACTICE OF NORDIC WALKING IN THE CONTEXT OF TOURISM AND ACTIVE LEISURE - Ščedrovienė, Jelena; Vanagienė, Salomėja (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The purpose of this article is to determine what forms of active leisure and tourism activities are being chosen by representatives of various groups of society in Lithuania and to find out the importance of Nordic walking in the context of active tourism and leisure. The pandemic, which lasted for several years, limited the opportunities of Lithuanians to travel abroad, but encouraged the search for new forms of leisure in Lithuania. A wider offer of local excursions appeared, more and more Lithuanians became interested in Nordic walking and other forms of active leisure. The research showed that a majority of respondents take part in hiking, water sports and cycling. All these activities are extremely popular during the warmer seasons. Meanwhile, Nordic walking is just beginning to establish itself as a popular form of active leisure